Climate variability along the margin of the southern African monsoon region at the end of the African Humid - (:unkn) unknown (My University, 2022)
Evidence for climate variability in the Southern African monsoon region (SAMR) is limited by a spatially and temporally discontinuous palaeoclimatic dataset. We describe a 6680 year long, largely sub-decadal resolution δ 15 N record from a rock hyrax midden from southeastern Africa. The results provide a detailed reconstruction of regional hydroclimates since the beginning of the mid-Holocene. A long-term-albeit subtle-increase in humidity consistent with precessional forcing is observed, but the record is dominated by a strong ~1750-yr cycle, a signal that is shared with other SAMR records. Considered in their regional context, these data suggest that changes coincident with the termination of the African Humid Period at ~5500 cal BP do not express the abrupt transition observed in some records from the northern African tropics. Rather they indicate gradual changes, as observed at peri-equatorial sites. Notably, however, eastern and western subregions of the SAMR experience a rapid phase shift beginning ~5500 cal BP, with initially in-phase hydroclimate anomalies transitioning to the establishment of a strong east-west dipole. This likely reflects a coeval strengthening of the Southeast Atlantic trade winds and decreased atmospheric pressure in southeast Africa, factors associated with increasing (decreasing) austral (boreal) summer insolation. The results highlight the distinct nature of southern African responses across this key period of African climate history.
Keywords: African Research